PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN LABA - Hermanda, Riza; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out and to prove the influence of financial ratio to the changes in earnings on agricultural companies which are listed in Indonesia Stock Changes in 2010-2013 periods. The ratios which are applied in this research are: current ratio, quick ratio, debt ratio, return on equity, dan total asset turnover.This research is Associative Quantitative research since this research tests whether the dependent variable (changes in earnings) has an influence to the independent variables (current ratio, quick ratio, debt ratio, return on equity, dan total asset turnover). The data has been obtained from the financial statement of agricultural companies. 12 companies are proper to be used as samples after they have passed the purposive sampling steps. The multiple linear regressions and classic assumption test which has been carried out by using SPSS 20 has been applied in this research as the data analysis technique. Based on the result of the analysis and hypothesis test it can be concluded that the determination coefficient value (R2) is 22.6%. It has been expected that the result of this research can be considered by the management to see the companyâs changes in earnings. Moreover, the result of the t test describes that current ratio and return on equity variables has an influence to the changes in earnings whereas quick ratio, debt ratio, total asset turnover variables do not have any influence to the changes in earnings. Simultaneously current ratio, quick ratio, debt ratio, return on equity and total asset turnover have an influence to the changes in earnings. Keywords: Current ratio, Quick ratio, Debt ratio, Return on equit, and Changes in Earnings